Shades of Complaint: Towards a Feminist Political Theology of Anger - Dege, Carmen Lea (Political theology, 2024)
This essay is a reflection on anger as a political emotion as well as the more recent turn towards a positive (re)evaluation of this passion. I distinguish between three attempts to conceptualize anger in contrast to the more dominant idea that anger is counterproductive and revenge-driven: (1) anger as essential knowledge in the struggle against injustice; (2) anger as an apt response to affective injustice; (3) anger as feminist attention that appreciates, rather than knows, injustice. I argue that a closer look at political theology in general and an apophatic hermeneutics in particular is especially helpful in evaluating these three approaches. It also allows for a reconceptualization of anger that moves beyond the traditional either/or choices in political theology such as those between friend and enemy, good and bad, or the sacred and the secular.